1996
DOI: 10.1080/713932612
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Locations in Working Memory in Cats

Abstract: Cats saw an object appear and disappear at two successive locations; the movement of the object from one location to the other was not perceived but was indicated by indirect cues and the two disappearances were separated by a 0-sec or a 20-sec interval. Performance was poorer with the 0-sec than with the 20-sec interval. With the 0-sec interval, the percentages of search attempts made at the object's initial and final hiding locations did not differ whereas with the 20-sec interval, more search attempts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…They found that between 0 and 10 s, the cats' performance in finding the hidden object rapidly declined, continued to decline at 30 s and remained only slightly above chance at 60 s. Therefore, despite differences in methodology, these results align with those of prior studies (Yarbrough 1917;Cowan 1923;Meyers et al 1962;Goulet et al 1996), suggesting the domestic cats' working memory may last as long as a minute, but rapidly declines over the 30 s following the object's disappearance.…”
Section: Object Permanence and Working Memorysupporting
confidence: 88%
See 1 more Smart Citation
“…They found that between 0 and 10 s, the cats' performance in finding the hidden object rapidly declined, continued to decline at 30 s and remained only slightly above chance at 60 s. Therefore, despite differences in methodology, these results align with those of prior studies (Yarbrough 1917;Cowan 1923;Meyers et al 1962;Goulet et al 1996), suggesting the domestic cats' working memory may last as long as a minute, but rapidly declines over the 30 s following the object's disappearance.…”
Section: Object Permanence and Working Memorysupporting
confidence: 88%
“…In order to solve the invisible displacement test, the subject must recognize the object is no longer in the container, that it must have been removed behind the obstacle, and search for the object at this location (Miller et al 2009). The majority of research has indicated that cats are unable to represent invisible displacement of an object (Doré 1986(Doré , 1990Goulet et al 1994Goulet et al , 1996 although Dumas (1992) found that cats successfully solved the invisible displacement test when a different, more species-relevant, methodology was used. In this version of the test, the cat was presented with an apparatus made of transparent and opaque screens, with a piece of food attached to a transparent string.…”
Section: Object Permanence and Working Memorymentioning
confidence: 96%
“…Task S is a variant of the "shell game": An object is visibly hidden under one of three covers, and the experimenter then visibly exchanges the position of this cover with one of two others. Whether Task S should be the defining criterion for Stage 6 is unclear because it also tests attention, different types of memory, and spatial cognition (see Goulet, Doré, & Lehotkay, 1996). The task nevertheless provides information about cognitive capacities.…”
Section: Details Ofmentioning
confidence: 99%
“…How Griffin's concurrent mirror exposure might have improved his performance is unclear. 13 9 We did not administer all the tests described by Dore' et al (1996) because our subjects succeeded on the most difficult ones. 10 Conceivably, Griffin's behavior could reflect insight learning (e.g., Kohler, 1927Kohler, /1976) but such a process is, by definition, different from trial-and-error learning.…”
Section: Environmental Influencesmentioning
confidence: 99%
“…Experiments on object permanence and search behavior in animals (for a review, see Doré & Dumas, 1987) have shown that nonhuman primates (de Blois & Novak, 1994; Mathieu, Bouchard, Granger, & Herscovitch, 1976; Natale, Antinucci, Spinozzi, & Poti, 1986; Parker, 1977; Redshaw, 1978; Wood, Moriarty, Gardner, & Gardner, 1980) as well as others vertebrates, such as cats (Doré, 1986, 1990; Dumas & Doré, 1989, 1991; Goulet, Doré, & Rousseau, 1994; Gruber, Girgus, & Banuazizi, 1971; Thinus-Blanc, Poucet, & Chapuis, 1982; Triana & Pasnak, 1981), dogs (Gagnon & Doré, 1992, 1993, 1994; Triana & Pasnak, 1981), and psittacids (Pepperberg & Funk, 1990, Pepperberg & Kozak, 1986), were able to find an object they saw move and disappear at different locations within the same trial or from trial to trial. Goulet et al (1994) and Goulet, Doré, and Lehotkay (1996) examined, in domestic cats, the conditions under which a hiding location was represented in working memory as well as the factors that determined the level of activation of successive hiding locations within a trial. In the present research, we investigated the type of spatial information that cats encoded and used when they saw an object disappear and the relative flexibility of spatial encoding in this species.…”
mentioning
confidence: 99%